Energy-driven damage evolution and instability in fissure-cavity-contained granite induced by freeze-thaw and multistage increasing-amplitude cyclic (F-T-MSIAC) loads. (March 2023) - Wang, Yu; Han, Jianqiang; Xia, Yingjie; Zhang, Bo
Rock damage and fracture is energy-driven, the energy conversion characteristics for the pre-flawed rock under static or fatigue loading conditions have been well widely studied. However, energy mechanism of rock containing fissures and hollow hole exposed to coupled freeze-thaw and cyclic loads is not well understood. In this work, damage and fracture evolution of pre-flawed hollow-cylinder granite specimens induced by freeze-thaw and multistage increasing-amplitude cyclic (F-T-MSIAC) loads were investigated using energy analysis. Testing results show that the volumetric deformation of rock is affected by the previous freeze-thaw cycles. Rock volumetric deformation decreases with increasing freeze-thaw cycle. The elastic strain energy and dissipated strain energy both decreases with increasing freeze-thaw cycles. When rocks undergo relatively small freeze-thaw cycles, a large amount of energy is consumed to drive crack propagation and cavity collapse. A coupling damage evolution model considering the freezing-thaw and mechanical damage was proposed. The model fits well to the two-stage and three-stage damage accumulation pattern. Two-dimensional CT images reveal different fracture network morphology and the effect of freeze-thaw weathering on crack coalescence. The results show that rock fracture is easy to occur under high freeze-thaw cycles, and less energy is required to communicate the fissures and hollow hole.